2005
DOI: 10.1111/j.0149-6085.2005.25552.x
|View full text |Cite
|
Sign up to set email alerts
|

INACTIVATION OF ESCHERICHIA COLI O157:H7 DURING THE STORAGE UNDER REFRIGERATION OF APPLE JUICE TREATED BY PULSED ELECTRIC FIELDS

Abstract: The sensitivity of pulsed electric fields (PEF)-treated E. coli O157:H7 cells to subsequent holding in apple juice has been evaluated. Escherichia coli O157:H7 cells in apple juice were resistant to PEF. A PEF treatment of 400 m s at any electrical field strength was not sufficient to inactivate one log 10 cycle of cells. However, PEF injured a large proportion of E. coli O157:H7 cells that became sensitive to a subsequent storage under refrigeration in apple juice. The total lethal effect of the combined proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 25 publications
3
31
0
Order By: Relevance
“…The study of the evolution of survival counts in refrigerated apple juice after MTS treatments was encouraged, among other reasons, because we supposed that its acidic pH would lead to the death of sublethally damaged cells caused by MTS as already observed with Escherichia coli for others technologies such as high pressure (García-Graells, Hauben, & Michiels, 1998) or pulsed electric fields (García, Hassani, Mañas, Condón, & Pagán, 2005), which would provide an additional advantage for acidic products. Results obtained indicate that C. sakazakii cells progressively died during refrigerated storage, but even upon 96 h, a certain proportion of cells still remained damaged in their cytoplasmic and outer membranes.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the evolution of survival counts in refrigerated apple juice after MTS treatments was encouraged, among other reasons, because we supposed that its acidic pH would lead to the death of sublethally damaged cells caused by MTS as already observed with Escherichia coli for others technologies such as high pressure (García-Graells, Hauben, & Michiels, 1998) or pulsed electric fields (García, Hassani, Mañas, Condón, & Pagán, 2005), which would provide an additional advantage for acidic products. Results obtained indicate that C. sakazakii cells progressively died during refrigerated storage, but even upon 96 h, a certain proportion of cells still remained damaged in their cytoplasmic and outer membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Possible recovery of the bacterial cells after treatment was investigated by spreading the samples on modified TSA (addition of 3% sodium chloride that is broadly in agreement with the method used by García et al 2005) in the same manner as stated before and extending the incubation period to 48 h. The amount of sublethally injured cells was estimated by comparing the bacterial counts after 24 h growth on non-selective TSA to the counts after 48 h on selective, modified TSA.…”
Section: Microbiological Preparation and Countsmentioning
confidence: 99%
“…It has also been demonstrated that sublethally PEF-injured cells lose viability during subsequent storage under acidic conditions. Consequently, the combination of PEF treatment applied to apple juice and subsequent storage under refrigeration for 48 h guarantees the inactivation of at least log 10 5 cell cycles of the pathogen Escherichia coli O157:H7 (12).…”
mentioning
confidence: 99%
“…Combined processes using PEF treatment must incorporate conditions that prevent the repair of cell envelopes (10,12) by the addition of food preservatives (7,9,14,18,19,23). Permeable membranes resulting from PEF treatment may facilitate the entry of antimicrobial compounds, such as organic acids, thereby increasing the antimicrobial action of the compounds (19).…”
mentioning
confidence: 99%